2017
DOI: 10.1520/gtj20160145
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Consequences of Suffusion on Undrained Behaviour of a Gap-Graded Cohesionless Soil - An Experimental Approach

Abstract: Fine particles may migrate in the preexisting pores of an internally unstable soil matrix caused by water flow. This migration changes the fine particle distribution and content at different zones and can affect the mechanical properties of these soils. Due to the different roles that fine particles can play in the force chains of an internally unstable soil, the available geometrical assessment methods do not predict post-erosion behavior of the soil. The fine particles may sit loose in the voids, provide lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 36 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…The increased initially with a decrease in (a ( ) decrease of the residual fine content down to 15.1 per cent) and then decreased with further reduction in equivalent intergranular contact index (decrease in the residual fine content down to 6.9 per cent). Mehdizadeh et al (2017a) showed that for the soil mixture used in this research coarse particles were more angular than fine particles. Therefore, the initial improvement in the undrained shear strength (initial peak shear stress, in Table 3) could be due to a better ′ interlock between the coarse particles but without the loss of semi-active fine particles which helps to prevent collapse at small strains.…”
Section: R a F Tmentioning
confidence: 74%
See 4 more Smart Citations
“…The increased initially with a decrease in (a ( ) decrease of the residual fine content down to 15.1 per cent) and then decreased with further reduction in equivalent intergranular contact index (decrease in the residual fine content down to 6.9 per cent). Mehdizadeh et al (2017a) showed that for the soil mixture used in this research coarse particles were more angular than fine particles. Therefore, the initial improvement in the undrained shear strength (initial peak shear stress, in Table 3) could be due to a better ′ interlock between the coarse particles but without the loss of semi-active fine particles which helps to prevent collapse at small strains.…”
Section: R a F Tmentioning
confidence: 74%
“…The particle size distribution and physical properties of the soil mixture are shown in Fig. 1 Mehdizadeh et al (2017a) showed that angularity of particles in coarse fraction is higher than that of fine fraction which may enhance the erosion resistance as stated by Marot et al (2012). On the other hand, erosion of the more rounded fines will lead to an overall increase in the average angularity of particles and therefore an increase in post-erosion interlocking.…”
Section: Testing Programmentioning
confidence: 94%
See 3 more Smart Citations